The space tourist's handbook where to go, what to see, and how to prepare for the ride of your life - Anderson, Eric; Piven, Joshua (Quirk Books, 2005)
Provides practical information for would-be space tourists, describing different types of flights and covering flight training, the launch, emergencies, and such aspects as sleeping in weightless environments and using the vacuum toilet -- Source other than Library of Congress.